FOREST FIRE RISK MAPPING IN THE CERRADO: an integrated management approach in Tres Lagoas - Oliveira, Vincler de; Silva, Edson da; Vick, Erivelton; Silva, Bruno da; Sato, Amanda; Bacani, Vitor; Lima, Cesar [UNESP]; Silva, Agnaldo; Chavez, Eduardo (Univ Estado Rio Janeiro, 2024)
Forest fires cause numerous environmental changes, such as reduced biodiversity, soil loss, loss of vegetation and, consequently, increased deforestation. The main objective of this work is to evaluate the risk of forest fires, in the Brazilian Cerrado region that presents a strong forest expansion, using Geographic Information Systems. To this end, eight environmental and sociocultural variables are used to identify the areas most susceptible to forest fires, which are: built area (Ac); slope (D); hydrography (Hello); access point (Ho); slope orientation (Ov); precipitation (P); proximity to the road network (Prv) and land use and cover (U), which were evaluated in the GIS using cartographic algebra. The results show the predominance of the medium fire risk, with 72.30% of the total area of the municipality of Tr & ecirc;s Lagoas. The low fire risk represents just over 22%, while the high risk covers only 4.89% of the municipality. This shows that the municipality presents fire risks that can be managed through mapping. Since there is a greater risk in the months of June, July and especially August and September, which requires special attention due to low rainfall and the increase in the average concentration of outbreaks.
Keywords: Geographic Information System; forest fire risk mapping; map algebra; Mato Grosso do Sul